Konsep Matematika Kerajinan Kayu Pada Perabotan Rumah Tangga: Eksplorasi Etnomatematika - indah rahayu; Widatul Istiqomah; Nur Hidayatin (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2026)
Mathematics is a branch of science that studies numbers and shapes. In everyday life, community activities unconsciously apply mathematical concepts. Ethnomathematics is a field of study that integrates local culture with mathematical concepts. This research aims to explore forms of ethnomathematics related to woodcraft. Woodcraft is a type of handicraft that primarily uses wood as its main material. The type of research used in this study is descriptive research with an ethnographic design, aimed at understanding the mathematical aspects contained from an ethnomathematical perspective. The application of ethnomathematics in the learning process can enrich teaching materials by connecting mathematical concepts with the cultural backgrounds of students. The method employed in this research is an ethnographic approach, in which data are collected through observation, interviews, and documentation. Keywords: etnomathematic, woodcraft